Clustered swarm : a live swarm‐based traffic load balancing algorithm against traffic jams. Issue 3 (23rd September 2016) - Stolcis, Christian; Pfannerstill, Elmar
Abstract : Traffic jam. A phenomenon representing one of the biggest and most interesting problems of the 21st century. More than 60% are caused by too many vehicles using the common resource 'road'. General countermeasures and individual route calculation approaches could not solve the problem until now and can even cause traffic jams under certain circumstances. Current research and developments in the area of mobile communication and car‐IT like vehicle to vehicle communication open up new perspectives in the fight against the expected traffic gridlock. This study introduces a concept and a first implementation of a live swarm‐based algorithm which pursues the aim of a global traffic optimisation by performing a massive load balancing of all road participants to improve the individual routes for the users and thereby represents a potential solution for the traffic jam problem.